Ibero-American architecture journals in Web of Science (2017-2019): analysis of their internationality and visibility - Mochón-Bezares, Gonzalo; Sorli-Rojo, Ángela (Revista General de Información y Documentación, 2022)
This work analyzes the internationality of the Ibero-American journals on architecture collected in the Web of Science databases in 2017, 2018 and 2019. A total of 1528 articles from 24 periodical publications on architecture, 6 of them included in the Arts & Humanities Citation Index and the rest in the Emerging Sources Citation Index. The following parameters are analyzed: production of authors from foreign institutions on the total published and their degree of collaboration, languages ​​used in the writing of articles, institutional affiliation of members of editorial teams, presence of journals in secondary sources of information. The results show a low number of foreign authors and a minimal international collaboration, little use of English in the writing of articles, a majority of foreigners among the members of editorial teams, and a limited presence of many journals in the analyzed information sources, especially in databases on architectural themes. It is concluded that to improve their level of internationality, the Ibero-American architectural periodicals present in the Web of Science should increase collaboration among authors from different countries, increase the publication of works in English, and improve their presence in databases on architectural themes.